Photocatalytic evaluation of chitosan and its derivative coated vanadium pentoxide nanoparticles for photodegradation of methylene blue - Bansal Smriti; Jain Purnima (E3S Web of Conferences, 2024)
Vanadium pentoxide (V2O5) is widely utilized as a photocatalyst for the degradation of various pollutants due to its narrow bandgap and convertible oxidation states of vanadium. Here, V2O5 nano-adsorbents coated with functionalized chitosan exhibit a great sensitivity to the absorption of visible light that makes them a suitable candidate to study the photodegradation of methylene blue in the natural atmosphere. Characterization results revealed the synthesis of chitosan-anisaldehyde Schiff base and its presence over the surface of nanoparticles. Fabricated nanoparticles exhibited enhanced optical band gap that increases the photodegradation efficiency by reducing the recombination rate as well as they possess an orthorhombic crystalline phase as confirmed by XRD. Among all fabricated nanoparticles, one of the coated nano-adsorbents, chitosan-anisaldehyde adorned V2O5 (CHA1), having wedge-shaped pores that aided in the photocatalytic destruction of methylene blue illustrates the best degradation efficiency as compared to the bare ones.